Preparation and Characterization of Lanthanum (III) Selective Electrode Based on 1,10-Diaza-4,7,13,16-Tetraoxacyclooctadecane-N,N'-Diacetic Acid as an Ionophore - Suyanta Suyanta; Susanto I.R; Buchari Buchari; Indra Noviandri (Jurnal Pendidikan Matematika dan Sains, 2006)
The preparation and characterization of lanthanum (III) ion selective electrode based on the 1,10-diaza-4,7,13,16-tetraoxacyclooctadecane-N,N'-diacetic acid as ionophore was studied. The electrode was prepared with an inner solution system in a membrane composition that contained active DACDA ionophore, the anionic side of KTCPB, the plasticizer of NPOE and a PVC matrix support. The good response was obtained with a slope of 19.53 +- 1.62 mV/decade and a good correlation between potential and lanthanum (III) concentration. Electrode could response with a detection limit of 3.92x10^-6 M and range measurement between 10^-5 M to 10^-1M. Electrode is steady at pH 4-9 and the best condition of inner solution concentration at 10^-3 M. Response time was 27.1 seconds and their life time was 50 day.Kata kunci: lanthanum ion-selective-electrode, PVC membrane, 1,10-diaza-4,7,13,16-tetraoxacyclooctadecane-N,N'-diacetic acid